Recursion and Noticing In Written Feedback - Kumar, Vijay; Kumar, Margaret (EuroJournals Publishing, Inc., 2009)
Though written feedback is one of the widely researched area in second language writing, cognitive processes of student writers as they attend to teacher feedback is still in its infancy. Previous researches have concentrated mostly on the types of feedback, the teacher or the student writers. Teachers need to understand writers’ behaviors to intervene. There is a paucity of literature on the actual thought processes that occurs when a writer attends to written teacher feedback at a particular moment of time. This exploratory study provides a window to two important thought processes of a writer; recursiveness and noticing which have pedagogical implications.